2016
DOI: 10.3233/ves-150564
|View full text |Cite
|
Sign up to set email alerts
|

Falls and fear of falling in vertigo and balance disorders: A controlled cross-sectional study

Abstract: Falls are common in patients presenting to a dizziness unit. Those with central syndromes are at risk of recurrent and injurious falling. Fall rates and fear of falling should be assessed in balance disorders and used to guide the regimen of rehabilitation therapy. The identification of risk factors would help provide protective measures to these groups of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
77
0
14

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(97 citation statements)
references
References 38 publications
6
77
0
14
Order By: Relevance
“…Thus, a cerebellar dysfunction during migraine attacks can be deduced by (i) an increased postural sway at baseline (condition 1) and (ii) the absence of increased RQs. Similarly, the lack of a firm support beneath the feet has been shown to destabilize patients with either vestibular or proprioceptive deficits . Using foam posturography, these studies demonstrated high vRQ values in patients compared to healthy controls.…”
Section: Discussionmentioning
confidence: 95%
“…Thus, a cerebellar dysfunction during migraine attacks can be deduced by (i) an increased postural sway at baseline (condition 1) and (ii) the absence of increased RQs. Similarly, the lack of a firm support beneath the feet has been shown to destabilize patients with either vestibular or proprioceptive deficits . Using foam posturography, these studies demonstrated high vRQ values in patients compared to healthy controls.…”
Section: Discussionmentioning
confidence: 95%
“…90 It is also an important concern for people with vestibular disorders. 91 Honaker and Kretschmer 92 conducted a qualitative study to examine how fear of falling changed after VR in individuals with vestibular and balance disorders who had a history of falling. 92 In this sample, fear of falling resulted in restricting the performance of activities of daily living.…”
Section: Fear Of Fallingmentioning
confidence: 99%
“…u geriatrického pacienta s akútnym neurologickým ochorením a s poruchami chôdze sa riziko násobí pri pozitívnej anamnéze pádu a používaní kompenzačnej pomôcky [10]. Riziko pádu alebo samotný pád je symptómom klinického obrazu viacerých neurologických ochorení (skleróza multiplex, demencia, Parkinsonova choroba, záchvatové stavy, cievna mozgová príhoda, ochorenia vestibulárneho aparátu, periférne neuropatie), pričom mechanizmus pádu je špecifický pre každé z nich [9,14,15]. Klinické symptómy spolu s pozitívnou anamnézou pádu zaraďujú pacienta už pri prijatí na hospitalizáciu do skupiny s vysokým rizikom pádu, bez ohľadu na to, či sú prijatí s akútnou alebo chronickou neurologickou diagnózou [5,7,16,17].…”
Section: úVodunclassified